Rather complements than substitutes: Firm value effects of capital structure and financial hedging decisions - Markus Hang; Jerome Geyer-Klingeberg; Andreas W. Rathgeber; Stefan Stöckl (International Journal of Finance & Economics, 2021)
The aim of this study is to analyze the interaction between capital structure decisions and risk management decisions as well as the channels through which they add value to firms. Competing theories are considered in an integrated path model, which we test by means of meta-analytic structural equation modelling (MASEM). This meta-analysis is based on 6,312 reported results, which are manually collected from 411 empirical studies. We find that capital structure mediates the relation between corporate financial hedging and firm value. In this regard, active risk management positively affects leverage by providing greater debt capacities. Furthermore, leverage has a negative impact on firm value. Hence, capital structure and financial hedging decisions appear rather as complements instead of substitutes. This implies that managers should leave additional debt capacities unused and instead use additional internal funds arising from active risk management to carry out profitable projects and research and development activities. Overall, corporate hedging is found to especially add value to a firm by lowering bankruptcy risks and underinvestment risks.
Keywords: 330; capital structure; firm value; meta-analysis; risk management; structural equation model